2001
DOI: 10.1016/s0014-5793(01)02764-8
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of neuroserpin: a neuronal serpin involved in a conformational disease

Abstract: The protease inhibitor neuroserpin regulates the development of the nervous system and its plasticity in the adult. Neuroserpins carrying the Ser53Pro or Ser56Arg mutation form polymers in neuronal cells. We describe here the structure of wild-type neuroserpin in a cleaved form. The structure provides a basis to understand the role of the mutations in the polymerization process. We propose that these mutations could delay the insertion of the reactive center loop into the central L L-sheet A, an essential step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…NS, human neuroserpin; CyC, cytochrome c; CNX, calnexin. conformational stability of the molecule (11,16). Deduced from other members of the serpin family, the mutations in neuroserpin give a predictable gradation of conformational instability: G392E Ͼ H338R Ͼ S52R Ͼ S49P (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NS, human neuroserpin; CyC, cytochrome c; CNX, calnexin. conformational stability of the molecule (11,16). Deduced from other members of the serpin family, the mutations in neuroserpin give a predictable gradation of conformational instability: G392E Ͼ H338R Ͼ S52R Ͼ S49P (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…The S52R neuroserpin was trapped as an inactive intermediate that rapidly formed polymers in vitro (15). Crystal structures of neuroserpin indicated sequential insertion of the reactive center loop of one molecule into ␤-sheet A of another (16). Cell transfection studies in COS-7 cells have shown that mutant neuroserpin (S49P and S52R) is retained within the endoplas-mic reticulum (ER) as polymers (17).…”
mentioning
confidence: 99%
“…22 Despite the considerable medical interest in hNS, to date only a 3.06 Å resolution structure of cleaved mouse neuroserpin has been reported. 23 Such lack of direct structural information prompted us to investigate the crystal structures of hNS in its native and cleaved forms, reported here at 3.15 and 1.85 Å resolution, respectively. Moreover, although the instability of the hNS-tPA complex over time had been previously recognized, the relative lack of kinetic studies taking into account the limited temporal stability of the complex for the analysis of the data led us to reconsider an investigation on tPA inhibition kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…These polymers tangle to form periodic acid-Schiff-positive, diastase-resistant inclusions that are associated with neonatal hepatitis, juvenile cirrhosis, and hepatocellular carcinoma (33). It was very striking that the mutations that underlie FENIB were in the same shutter domain of the serpin molecule as those that caused polymerization of ␣ 1 -antitrypsin with accompanying liver disease (8,34). Indeed, the examination of protein from the brains of affected individuals demonstrated that the inclusions were composed solely of mutant neuroserpin and that this had formed chains of loop-sheet polymers identical to those of mutant ␣ 1 -antitrypsin, which accumulate within the liver (8,9,35).…”
mentioning
confidence: 99%